Lietuviškosios religinės tapatybės raiškos užuomazgos ir jų ženklai XVII amžiaus LDK poezijoje: M. K. Sarbievijaus religinės tematikos tekstai - Daukšienė, Ona (Literatūra, 2015)
The subject-matter of this research is a Latin religious poetry written at the 17th century, primarily by Jesuit authors, in the Grand Duchy of Lithuania. The texts analysed in the paper are seen as important to the further formation of Lithuanian religious identity and its poetical expression. It is possible to trace the influence of some Baroque Latin texts, especially of those written by M. C. Sarbievius (Sarbiewski), the most popular Latin poet in Lithuania through following centuries, on the religious poetry of the 19th century. Some topics, as presented in the later religious texts and often being explained as a mere reflection of Romantic discourse, seem to be derived from the baroque expression.